2012
DOI: 10.1371/journal.pone.0051829
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Human Dicer-dsRBD in Processing Small Regulatory RNAs

Abstract: One of the most exciting recent developments in RNA biology has been the discovery of small non-coding RNAs that affect gene expression through the RNA interference (RNAi) mechanism. Two major classes of RNAs involved in RNAi are small interfering RNA (siRNA) and microRNA (miRNA). Dicer, an RNase III enzyme, plays a central role in the RNAi pathway by cleaving precursors of both of these classes of RNAs to form mature siRNAs and miRNAs, which are then loaded into the RNA-induced silencing complex (RISC). miRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 64 publications
4
41
0
Order By: Relevance
“…GST alone did not bind any of the tested dsRNAs (data not shown). Recently, another study reported the RNA-binding characteristics of the human Dicer dsRBD as an isolated domain, comparing it to the first dsRBD of DGCR8 (Wostenberg et al 2012). The reported K d values for Dicer-dsRBD ranged from ∼2 to 10 μM, with the affinity of binding decreasing with decrease of the substrate length, which is similar to our findings.…”
Section: Dsrbd Integrity But Not Rna-binding Potential Is Essentialsupporting
confidence: 89%
See 2 more Smart Citations
“…GST alone did not bind any of the tested dsRNAs (data not shown). Recently, another study reported the RNA-binding characteristics of the human Dicer dsRBD as an isolated domain, comparing it to the first dsRBD of DGCR8 (Wostenberg et al 2012). The reported K d values for Dicer-dsRBD ranged from ∼2 to 10 μM, with the affinity of binding decreasing with decrease of the substrate length, which is similar to our findings.…”
Section: Dsrbd Integrity But Not Rna-binding Potential Is Essentialsupporting
confidence: 89%
“…However, this study also showed that deletion of the dsRBD did not significantly affect binding of the truncated protein to RNA . Our data and those of Wostenberg et al (2012) demonstrate that human Dicer dsRBD binds dsRNA with low micromolar or sub-micromolar affinity for RNA, hence less efficiently when compared to a dsRBD that has robust RNA-binding potential, e.g., dsRBD2 of XlrpA. Therefore, although Dicer's dsRBD likely contributes to binding of substrate RNA, its exact role in dsRNA processing still remains to be determined.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…For the long ds44 and ds33 constructs, in vitro transcription using a duplex method, followed by purification, was performed as previously described [23]. The shorter ds22 RNA strands were purchased from Dharmacon and deprotected using the manufacturer protocol prior to duplex formation.…”
Section: Methodsmentioning
confidence: 99%
“…The PAZ/Platform, dsRBD and RNase III domains are involved in dsRNA binding and cleavage. In particular, PAZ and Platform domains enfold binding pockets for the 3 0 -overhang and 5 0 -phosphate moieties of the dsRNA substrate, respectively [3]; dsRBD domain binds the dsRNA [4]; RNase IIIa and IIIb domains function as an intramolecular pseudo-dimer forming a single processing centre containing two independent catalytic ''half sites'', with the RIIIa domain cleaving the 3 0 pre-miRNA arm, and RIIIb cleaving the 5 0 arm of pre-miRNA [5]. The helicase domain has a role in the control of enzyme activity [6] and interacts with the two dsRBD-containing cofactors of Dicer in RISC loading complex (RLC), i.e., TRBP and PACT, involved in siRNA-induced RNAi and in miRNA accumulation [7][8][9].…”
Section: Introductionmentioning
confidence: 99%